A Breakthrough Improvement Collaborative Significantly Reduces Hospital Stay After Elective Colectomy for Cancer Across a Healthcare System. Issue 5 (2nd November 2022) - Coeckelberghs, Ellen; Vanhaecht, Kris; Seys, Deborah; Cox, Bianca; Bislenghi, Gabriele; Wolthuis, Albert M.; D'Hoore, André; ,
Abstract : Objective: This multicenter study aimed to assess (1) the effect of an improvement collaborative on enhanced recovery after surgery (ERAS) protocol adherence after elective colectomy and (2) the association between adherence and patient outcomes. Background: ERAS pathways provide a framework to standardize care processes and improve postoperative outcomes in patients after colon surgery. Despite growing evidence of its effectiveness, adherence to these guidelines remains a challenge. Methods: This prospective, multicenter collaborative was initiated throughout 11 hospitals in Flanders, Belgium. A structured audit tool was used to study patient outcomes and adherence to 12 ERAS components, defined by the collaborative. Three retrospective audits (based on patient record analysis) were conducted in 2017, 2019, and 2021, respectively. Results: Overall, 740 patients were included (45.4% female; mean±SD age, 71±12 years). The overall adherence increased from 42.8% in 2017 to 58.4% in 2019 and 69.2% in 2021. Compared with low adherence, length of stay was increasingly reduced by 1.3 days for medium [95% confidence interval (95% CI): −2.5; 0.0], 3.6 days for high (95% CI: −4.9; −2.2), and up to 4.4 days for very high adherence (95% CI: −6.1; −2.7). Corresponding odds ratios for postoperative complications were 0.62 (95% CI: 0.33; 1.17), 0.19 (95% CI: 0.09; 0.43), and 0.14 (95% CI: 0.05; 0.39), respectively. No increase in 30-day readmissions was observed. Conclusions: A peer-constructed improvement collaborative effectively increases adherence to an ERAS protocol in individual hospitals. Across time, length of stay and postoperative complications decreased significantly, and a dose-response relationship was observed.